Identification and profiling of miRNAs during herbivory reveals jasmonate-dependent and -independent patterns of accumulation in Nicotiana attenuata - Bozorov Tohir A; Baldwin Ian T; Kim Sang-Gyu (BMC Plant Biology, 2012)
Abstract Background Plant microRNAs (miRNAs) play key roles in the transcriptional responses to environmental stresses. However, the role of miRNAs in responses to insect herbivory has not been thoroughly explored. To identify herbivory-responsive miRNAs, we identified conserved miRNAs in the ecological model plant Nicotiana attenuata whose interactions with herbivores have been well-characterized in both laboratory and field studies. Results We identified 59 miRNAs from 36 families, and two endogenous trans-acting small interfering RNAs (tasiRNA) targeted by miRNAs. We characterized the response of the precursor and mature miRNAs to simulated attack from the specialist herbivore Manduca sexta by quantitative PCR analysis and used ir-aoc RNAi transformants, deficient in jasmonate biosynthesis, to identify jasmonate-dependent and -independent miRNA regulation. Expression analysis revealed that groups of miRNAs and tasiRNAs were specifically regulated by either mechanical wounding or wounding plus oral secretions from M. sexta larvae, and these small RNAs were accumulated in jasmonate-dependent or -independent manners. Moreover, cDNA microarray analysis indicated that the expression patterns of the corresponding target genes were correlated with the accumulation of miRNAs and tasiRNAs. Conclusions We show that a group of miRNAs and tasiRNAs orchestrates the expression of target genes involved in N. attenuata’s responses to herbivore attack.